Desire for Continued Pessary Use Among Women of Hispanic and Non-Hispanic Ethnic Backgrounds for Pelvic Floor Disorders. Issue 2 (March 2019) - Gupta, Ankita; Cox, Carol; Dunivan, Gena C.; Gaskins, Jeremy T.; Rogers, Rebecca G.; Iglesia, Cheryl B.; Meriwether, Kate V.
Abstract : Objective: This study aimed to describe the association between patient ethnicity/race and desire to continue using a pessary for the treatment of pelvic floor disorders. Methods: We performed a secondary analysis of a randomized trial among women presenting for pessary fitting. The primary outcome was the desire to continue using a pessary at 3 months. Bacterial vaginosis by Nugent score and vaginal symptoms (discharge, itching, pain, sores) were also evaluated. Logistic or multiple linear regression was performed with correction for body mass index, education level, parity, Charlson Comorbidity Index, and randomization to TrimoSan gel. Results: One hundred fourteen women (41 Hispanic and 73 non-Hispanic) were eligible for this analysis. Women self-identified as white (65/114; 57%), Hispanic (41/114, 36%), Asian (3/114; 2.6%), Native American (4/114; 3.5%), and "other" (1/114, 0.9%) race, with no self-identified African American women (0/114) meeting the inclusion criteria. No significant difference in desire to continue pessary use was found between Hispanic and non-Hispanic women (58.5% vs 63%; P = 0.69; corrected odds ratio [cOR], 1.11; 95% confidence interval [CI], 0.43–2.90) or across races ( P = 0.89). Hispanic women had significantly higher risk of bacterial vaginosis (34% vs 16%; P = 0.04; cOR, 2.91; 95% CI, 1.01–8.39), higher Nugent scores (5.4 ± 2.3 vs 4.3 ± 2.3; P = 0.02; corrected coefficient, 1.10; 95% CI, 0.10–2.10), and more vaginal pain (17.1% vs 2.8%; P = 0.01; cOR, 9.14; 95% CI, 1.37–61.17) at 3 months. Conclusions: Despite increased vaginal pain and vaginal microbiome disturbances in Hispanic women using a pessary, no significant differences in the desire to continue using the pessary existed.